Da-Bu-Yin-Wan Improves the Ameliorative Effect of DJ-1 on Mitochondrial Dysfunction Through Augmenting the Akt Phosphorylation in a Cellular Model of Parkinson’s Disease - Zhang, Yi; Gong, Xiao-Gang; Sun, Hong-Mei; Guo, Zhen-Yu; Hu, Jing-Hong; Wang, Yuan-Yuan; Feng, Wan-Di; Li, Lin; Li, Ping; Wang, Zhen-Zhen; Chen, Nai-Hong (Frontiers in Pharmacology, 2018)
Da-Bu-Yin-Wan (DBYW) is recorded originally in China over six centuries ago, and it is used to treat Parkinson’s disease (PD) clinically in recent decades. DJ-1 is a homodimeric protein linked to early-onset PD, and found in the mitochondria. In addition, DJ-1 could protect the cells by regulating gene transcription and modulating the Akt signal pathways. Therefore, in this research, we aimed to investigate the ameliorative effect of DBYW on mitochondria in the view of the DJ-1 and Akt signaling. Rat adrenal pheochromocytoma cell line PC-12 was transfected with the plasmid pDJ-1. Subsequently, PC-12 cells were exposed to the PD-related mitochondrial toxin (1-methyl-4-phenylpyridinium) without/with the DBYW. After transfected with the plasmid pDJ-1, the 1-methyl-4-phenylpyridinium-induced toxicity was decreased, and the DJ-1 expression in protein level was increased. DJ-1 overexpression not only increased the mitochondrial mass, but also improved the total ATP content. Moreover, Akt phosphorylation was augmented by DJ-1overexpression. Additionally, DBYW enhanced the above effects. Conclusively, these findings indicate that DBYW promotes the ameliorative effects of DJ-1 on mitochondrial dysfunction at least through augmenting the Akt phosphorylation in 1-methyl-4-phenylpyridinium-treated PC-12 cells.